A Monte Carlo Modeling of Planetary Formation: A Case of 47 Ursae Majoris System - Avivah Yamani; Taufiq Hidayat; Ratna Satyaningsih; Budi Dermawan (Institut Teknologi Bandung, 2010)
This paper presents a Monte Carlo simulation, using Planetary System Generator, which has been built based on a simple accretion model by Dole (1970) and by considering the present structure of the Solar System. Data of known extrasolar planets have also been taken into account.Â Â It was then applied to generate 47 Ursae Majoris (47UMa)-like planetary systems. The results are subsequently compared to the observed data of 47UMa. The dynamical evolution as well as the stability of the system have been evaluated by using a n-body formalism accounted for in our simulation. The generated system reproduced approximately the observational data and suggests that some other accompanying planets may exist. The orbital evolution is also found to be stable within the current age of the system.